Association of residual feed intake with intestinal microbiome and metabolome in laying period of ducks - Sun, Hanxue; Xu, Wenwu; Gu, Tiantian; Sun, Jing; Li, Chengfeng; Chen, Li; Tian, Yong; Li, Guoqin; Lu, Lizhi; Zeng, Tao (Frontiers in Microbiology, 2023)
Residual feed intake (RFI) is a indicator to evaluate animal feed. This experiment was explored to study the relationship between intestinal microbiome and metabolome of ducks with different residual feed intake during laying period. A total of 300 Shaoxing ducks aged 42 weeks were randomly selected and fed a diet of 60 d. At the end of the trial, 20 samples were selected according to the phenotype of RFI and divided into two groups (HRFI and LRFI). The cecal microbiota composition was explored by 16S ribosomal RNA gene sequencing and rectal metabolomics uses liquid chromatography-mass spectrometry (LC-MS) to identify the composition of metabolites in a non-targeted manner. Results show feed intake and feed conversion ratio in the group HRFI were significantly higher than those in the group LRFI (p < 0.05). Chao1 indices were higher in the group LRFI than in the HRFI (p <0.05), Shannon and Simpson indices were higher in the group LRFI than in the HRFI (p <0.01). After linear discriminant analysis effect size (p < 0.05, LDA score > 3), Rikenellaceae, Rikenellaceae_RC9_gut_group, Lactobacillales and Ruminococcus_2, etc. were significantly enriched in the group LRFI at the genus level, while Prevotellaceae_NK3B31_group and Bacteria were significantly enriched in the group HRFI. After LC-MS analysis we found 338 metabolic difference products and 10 metabolic pathways, including the ABC transporter system, cysteine and methionine metabolism, arginine and proline metabolism, and vitamin B6 metabolism, were identified to be associated with the significantly differentially expressed between the groups LRFI and HRFI (p <0.05). We hypothesize that the difference between ducks with different RFIs is mainly due to the fact that ducks with LRFI have more SCFAs-producing bacteria in their gut microorganisms, which regulate the RFI of animals. This process we found that Phascolarctobaterium and Anaerobiospirillum may provide energy for ABC transporter system by producing SCFAs, and regulate RFI to improve feed utilization efficiency. These results revealed the relationship between microbiome and metabonomics in laying ducks with different RFI, and provided theoretical basis for further study on the relationship between them.